Aggression and Gender - Mullins, Christopher (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This exercise is designed to get the students thinking and talking about aggression as it is manifest in men and women. It is designed to get them to question the stereotypes of aggressive men and passive women.